2020
DOI: 10.1177/1010539520928187
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Received Neighboring Behavior on General Health: The Mediating Role of Work-Family Conflict

Abstract: This study investigated the relationships between received neighboring behavior (ie, informal mutual assistance and information sharing among neighbors) and the general health of low-income residents in a mixed-income community. A conservation resource theory perspective was applied. Survey data were selected from a self-reported questionnaire of 247 low-income residents in a mixed-income community of China. A 2-wave panel design was used to test the hypothesized relationships among the studied variables, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A potential explanation for these inconsistent results may be the neglect of working residents' receiving neighboring behavior. Giving neighboring behavior is interpersonal and reciprocal (61) benefits of receiving neighboring behavior in relieving workfamily conflicts and facilitating mental health (22). Therefore, this paper explored how receiving and giving neighboring behavior fit impacts mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential explanation for these inconsistent results may be the neglect of working residents' receiving neighboring behavior. Giving neighboring behavior is interpersonal and reciprocal (61) benefits of receiving neighboring behavior in relieving workfamily conflicts and facilitating mental health (22). Therefore, this paper explored how receiving and giving neighboring behavior fit impacts mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have highlighted the benefits of receiving neighboring behavior on mental health. For instance, Zu et al suggested that assistance from neighbors will relieve workfamily conflicts, thereby enhancing mental health (22). Giving neighboring behavior is a process in which residents spend time helping others to resolve problems in the community (4).…”
Section: Literature Review and Hypothesis Development Congruence In R...mentioning
confidence: 99%
See 1 more Smart Citation